Digital Content Marketing for Enhancing Indonesia’s Tourism Industry - Adhika Putra Wicaksono; Bobby Ardiansyahmiraja; Muhammad Izharuddin (Integrated Journal of Business and Economics (IJBE), 2026)
Indonesia boasts numerous tourism destinations, supported by its rich cultural heritage, diverse natural attractions, and one of the world's largest archipelagos. The country's tourism sector is further strengthened by a substantial domestic tourism market driven by its large population. Meanwhile, digital technology has transformed the way tourism services are marketed and consumed. Digital Content Marketing (DCM) has emerged as an effective marketing tool that enables tourism stakeholders to engage consumers, build brand relationships, and influence travel decisions. Despite its growing importance, empirical research examining DCM in Indonesia's tourism context remains limited, particularly studies that extend the Technology Acceptance Model (TAM) by incorporating innovation and trust to explain travelers' behavioral intentions and actual usage. Therefore, this study develops an extended TAM framework to examine the influence of DCM on consumer behavior in Indonesia's tourism industry. A quantitative approach was employed using survey data collected from 298 Indonesian respondents, and the proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that 11 of the 12 proposed hypotheses are supported. Perceived ease of use, perceived enjoyment, and perceived convenience significantly influence attitudes toward using DCM, while attitude, innovation, and trust significantly affect behavioral intention, which subsequently drives the actual usage of DCM. However, the relationship between perceived usefulness and attitude is not statistically significant. These findings extend the application of TAM in the context of digital tourism marketing and provide practical insights for tourism stakeholders in designing innovative, trustworthy, and engaging digital content to encourage consumer travel decisions and support the sustainable growth of Indonesia's tourism industry.